Perianal Giant Condyloma Acuminatum—Buschke-Löwenstein Tumor: A Case Report. (20th November 2012) - Tas, Sukru; Arik, Muhammet Kasim; Ozkul, Faruk; Cikman, Oztekin; Akgun, Yilmaz
Abstract : Condyloma acuminatum caused by Human Papillomavirus is the most commonly occurring sexually transmitted infection in the anogenital region. Buschke-Löwenstein tumor (BLT) known also as giant condyloma acuminatum is a rare disease. The disease, for which the most important treatment method is the surgical excision, differs from normal condyloma acuminatum cases with its high degree of malignancy. The purpose of this paper is to present the case that reached huge dimensions in the perianal region and that was treated with wide resection in the literature.